The Prevalence of Swarming Genes in Escherichia coli Isolated from UTI and Catheter-Associated UTI - Hamza I. Kaittan; May T. Flayyih (مجلة كلية الطب)
Background: Urinary tract infections are one of the most common bacterial illnesses among the public and in hospital settings. A prevalent nosocomial disease is catheter-associated urinary tract infection (CAUTI). The risk of infection increases with urinary catheterization, making it easier for Escherichia coli to colonize the urinary system. Uropathogenic E. coli (UPEC) specifically adapts to survive in challenging urinary tract conditions. Treating CAUTI accurately and effectively can be difficult. An important health concern nowadays is drug-resistant bacteria.